The Protection of Selectively Bred and Gene Edited Farm Animals under EU Law - Ilaria Cimadori; Alice Di Concetto; Khara Grieger (European Journal of Risk Regulation)
Since the eighteenth century, animal breeding has significantly evolved, culminating in the use of gene editing (GE) technologies like CRISPR-Cas9. These technologies offer unprecedented capabilities to modify animal genomes, potentially revolutionising breeding practices by achieving desired traits much faster compared to traditional selective breeding (SB). Because breeding programmes focussed on productivity traits have often compromised animal welfare, this article provides an analysis of the ethical issues underpinning the use of GE in animal breeding, and the current laws regulating such practices. In doing so, this article critically examines the European Union (EU)’s regulatory framework for SB and GE in farm animals, highlighting significant gaps and inconsistencies. Specifically, the use of GE animals is currently regulated under the EU’s GMO legislation, while SB is more loosely regulated, posing substantial risks to animal welfare. The authors advocate for a regulatory framework that prioritises animal welfare goals and proposes reforms to enhance animal protection objectives by ensuring a more consistent and humane approach to farm animal breeding.